An extinct nestorid parrot (Aves, Psittaciformes, Nestoridae) from the Chatham Islands, New Zealand. (September 2014) - Wood, Jamie R.; Mitchell, Kieren J.; Scofield, R. Paul; Tennyson, Alan. J. D.; Fidler, Andrew E.; Wilmshurst, Janet M.; Llamas, Bastien; Cooper, Alan
<x xml:space="preserve">Abstract</x> We describe an extinct parrot from late Quaternary fossil bone deposits on the Chatham Islands, located c. 800 km east of mainland New Zealand. Mitochondrial DNA analyses and osteological characters confirm that the Chatham Islands parrot was a sister taxon to the New Zealand kaka (Nestor meridionalis Gmelin, 1788). The relatively large femur : humerus length ratio and broad pelvis of the Chatham Islands parrot indicate that it had a more terrestrial habit than the kaka. Stable dietary isotope analyses (δ 15N and δ 13C) of Chatham Islands parrot bones suggest that the species may have been mainly herbivorous, although further analyses are required to confirm this. The presence of Chatham Islands parrot bones in early midden deposits shows that the species persisted into the post‐settlement era, and became extinct possibly as a result of habitat loss, hunting pressure, and rat predation following initial Polynesian settlement of the islands (sometime between the 13th and 16th centuries AD). © 2014 The Linnean Society of London